TESTIMONY OF TRAUMATIC POLITICAL EXPERIENCES: THERAPY AND DENUNCIATION IN CHILE (1973-1985) - Lira, Elizabeth (Psyke & Logos, 2009)
This article shows how clinical practices developed during the military dictatorship led to new knowledge about trauma, particularly its effect on memory. Psychologists came up with the idea to have patients write down their testimony as a central element of their therapy. Patients embraced this. The shame and rage that was eating away at them could be channeled toward denouncing what had happened and demanding justice. Things changed in the 1980s: the public began to know about what was going on and the detainees’ stories found their way into the press. This »modified the place of denuncia and made the therapeutic process of giving testimony less necessary.« The last part of the work, shows the new social purpose written testimonies took on in the changing political climate of the 1980’s.